Design and characterization of short hybrid antimicrobial peptides from pEM‐2, mastoparan‐VT1, and mastoparan‐B. (5th October 2016) - Memariani, Hamed; Shahbazzadeh, Delavar; Ranjbar, Reza; Behdani, Mahdi; Memariani, Mojtaba; Pooshang Bagheri, Kamran
Abstract : Antimicrobial peptides are considered to be excellent templates for designing novel antibiotics because of their broad‐spectrum antimicrobial activity and their low prognostic to induce antibiotic resistance. In this study, for the first time, a series of short hybrid antimicrobial peptides combined by different fragments of venom‐derived alpha‐helical antimicrobial peptides pEM‐2, mastoparan‐VT1, and mastoparan‐B were designed with the intent to improve the therapeutic index of the parental peptides. Short hybrid antimicrobial peptides PV, derived from pEM‐2 and mastoparan‐VT1, was found to possess the highest antibacterial, hemolytic, and cytotoxic activity. Short hybrid antimicrobial peptides PV3, derived from pEM‐2 and three fragments of mastoparan‐VT1, showed more than threefold improvement in therapeutic index compared with parental peptides pEM‐2 and mastoparan‐VT1. PV had the highest antimicrobial activity in stability studies. Except BVP, designed based on all three parental peptides, the other short hybrid antimicrobial peptides at their minimal inhibitory concentration and 2× minimal inhibitory concentration required less than 120 and 60 min to reduce >3log10 the initial inoculum, respectively. All peptides had membrane‐disrupting activity in a time‐dependent manner. Collectively, this study highlights the potential for rational design of improved short hybrid antimicrobial peptides such as PV3 that was an ideal candidate for further assessment with the ultimate purpose of development of effective antimicrobial agents. Abstract : In this study, for the first time, a series of short hybrid antimicrobial peptides (SHAMPs) combined by different fragments of venom‐derived α‐helical antimicrobial peptides pEM‐2, mastoparan‐VT1 (MP‐VT1), and mastoparan‐B (MP‐B) were designed. All peptides had membrane‐disrupting activity in a time‐dependent manner. Collectively, current study highlights the potential for rational design of improved SHAMPs such as PV3 that was an ideal candidate for further assessment with the ultimate purpose of development of effective antimicrobial agents.